You want to rearrange the two given equations so that they add up looking like the target one.
For the first one: 2*(C + O2 --> CO2) = 2C + 2(O2) --> 2(CO2)
For the second one (reverse and multiply by 2) you get:
2*(CO2 --> CO + 1/2(O2) = 2(CO2) --> 2CO + O2
Adding up the two equations gives you the target one. Same idea with the delta Hs. For the first one you multiplied everything by 2 (the delta H as well). For the second delta H you change its sign and multiply it by two just like you did in the second equation. Then you add the two up (just like to get to the taraget equation):
2(-393.7KJ) + (-(2(-283.3KJ))) = -220.8KJ
Hope it helps. Buona fortuna